Pelaksanaan Eksekusi Hak Tanggungan Yang Dilakukan Kreditur Separatis Dalam Keadaan Insolvensi - Fathiya Achmad; Permata N. Daulay; Nurwidiatmo Nurwidiatmo (Postgraduate of Jayabaya University, 2017)
In the event of debtor’s bankruptcy, the separatist creditor must comply with the regulations of bankruptcy (UUK) and request of suspension of obligation for payment of debt (PKPU). Problems arise when the secured creditors interpret the articles on bankruptcy and PKPU differently from the Curators and other authorized bodies. Multi interpretation in those articles resulted in creditors’ losses because in the end the creditors will not be able to maximize the auction and must cede the bankrupted asets or properties to the Curator and wait for settlement proceeds after the Curator completes the preferred creditor. The method used in this research is a normative juridical research method supported by Empirical Juridical. The theory used as a tool to analyze is the theory of legal certainty by Gustav Radbruch and the legal protection theory by Philipus M Hadjon. It is concluded from the results of this study that the position of the Bank or also called by a separatist creditor in the execution of mortgages in bankruptcy is conditionally preceded and separated. The requirements stipulated as in the UUK and PKPU that the period of suspension (stay period) which is required to initially passed and the insolvency state.